The oxygen minimum zone relative depth is a key driver of dolphin habitats in the northern Humboldt Current System - Llapapasca, Miguel A.; Pardo, Mario A.; Grados, Daniel; Quiñones, Javier (Frontiers in Marine Science, 2022)
Highly mobile odontocetes need habitats with environmental conditions with the potential of aggregating enough and high-quality prey, to maximize foraging success. Until now, the characterization of those habitats was in terms of physical and biological indicators of high production, capable of attracting and sustaining prey. Nevertheless, there has been no approach to quantifying the effects of a biophysical characteristic of the ocean with proven effects on the vertical distribution of prey for cetaceans: The oxygen minimum zone (OMZ) depth. In the northern branch of the Humboldt Current System off Peru ( 6-18° S), a shallow OMZ (30-50 m) affects the distribution of the Peruvian anchovy (Engraulis ringens), main prey for several marine predators, including dolphins. We hypothesized these predators would aggregate in productive areas, but with preference for places where the relative OMZ depth can constrain prey vertically, making it more accessible and maximizing foraging success. We fitted Bayesian habitat models for three dominant odontocete species in this region, with multiple combinations of environmental covariates, smoothing techniques, and temporal and spatial random effects. Cetacean data came from 23 dedicated surveys spanning 2001-2019. Habitat predictors included the spatial anomalies of sea surface temperature, surface chlorophyl-a, pycnocline depth and OMZ depth. Dusky (Lagenorhynchus obscurus) and common dolphins (Delphinus delphis) preferred productive, cold areas with a very shallow OMZ, regardless of the season, while bottlenose dolphins (Tursiops truncatus) aggregated in both cold and warm waters, also with shallow OMZ. The former two species of higher metabolic demands would maximize energy intake by selecting areas with highly aggregated prey, while the latter, of more moderate metabolic needs and more diverse prey, would exploit less restricted habitats.